The plans of the protection tasks for the Natura 2000 areas as an instrument for environmental management - the key issues - Nowak, Maciej Jacek (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The article identifies key issues related to the implementation of the plans of protection tasks for the Natura 2000 area. Possible dilemmas concern both issues related to the formulation of the responsibilities for different subjects, as well as issues indicating local development plans and studies of conditions and directions of spatial development. Simultaneously, possible alternative solutions have been suggested.